2009
DOI: 10.2217/17460794.4.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Mother-to-Child Transmission of Hiv in Resource-Limited Settings

Abstract: Mother-to-child transmission (MTCT) before, during and after delivery may result in the acquisition of HIV for 30-35% of infants of HIV-infected mothers. Peripartum HIV transmission can be reduced to under 5% in resource-limited settings using a feasible prophylactic antiretroviral regimen. Reducing postnatal transmission through breastfeeding, whilst maintaining child survival, is an urgent priority, given that breastfeeding causes one-third to one-half of all infant HIV infections. Recent evidence highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…It has been shown that successful retention at all steps throughout the PMTCT cascade is paramount to effectively reduce vertical transmission [25, 3337]. The CHW-DT intervention in Tsholotsho failed to increase the share of such patients in the cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that successful retention at all steps throughout the PMTCT cascade is paramount to effectively reduce vertical transmission [25, 3337]. The CHW-DT intervention in Tsholotsho failed to increase the share of such patients in the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Modern PMTCT medication has proven to be highly efficacious and could lead to virtual elimination of paediatric HIV if universally implemented [15, 24, 32, 33]. This, however, would require high coverage and retention levels with timely service uptake at all recommended steps [25, 3337]. While some SSA countries, such as Botswana, Namibia or South Africa, demonstrate that universal PMTCT coverage is feasible in low-resource settings, most SSA countries show major gaps [7, 10, 14, 16, 24, 35].…”
Section: Introductionmentioning
confidence: 99%
“…These factors are known to increase the risk of vertical transmission. Mode of delivery, nutritional deficiencies, use of addictive drugs like tobacco, cocaine, heroin and opiates, breastfeeding and failure to initiate nevirapine/zidovudine (NVP/ZDV) prophylaxis in the exposed infants also affect transmission rate of HIV from mother to infant 7,8 .…”
Section: Chama Et Al In University Of Maiduguri Teachingmentioning
confidence: 99%
“…The 2001 National HIV Sentinel Surveillance Survey estimated that an antenatal nationwide HIV sero-prevalence of 29.5% acquire HIV from their mothers annually in Zimbabwe [5]. The authors in [6] reported that MTCT before, during and after delivery may result in the acquisition of HIV for 30–35% of infants of HIV-infected mothers.…”
Section: Introductionmentioning
confidence: 99%